Barriers and facilitators to mental health care: a systematic review in Pakistan - Choudhry, Fahad Riaz; Khan, Nashi; Munawar, Khadeeja (Taylor & Francis, 2021)
It is well documented that there is a shortage of mentalhealth care providers, mental health literacy, and underutiliza-tion of mental health services in Pakistan. This systematicreview aimed to assess the available evidence on factors hin-dering and/or facilitating access to care among people withmental health issues, health care providers, carers, or anyother population group (e.g., students, teachers) in Pakistan.Thirteen published studies of barriers and facilitators inPakistan were identified through nine electronic databases:Ovid MEDLINE, Ovid Embase, Ovid Emcare, CINAHL plus,Proquest Central, PsycInfo, Scopus, Pubmed, andScienceDirect. Thematic analysis revealed that factors facilitat-ing access to mental health services were trust in the effect-iveness of mental health services and acknowledging theseriousness of the problem. However, factors hindering theaccess were financial issues/constraints, personal issues/otherpriorities, stigma, low mental health knowledge, side-effects/dissatisfaction from previous treatments, time and distanceconstraints, reliance on traditional/religious healers, and lackof social (i.e., family and peers) support/encouragement.Findings suggest the need for reducing barriers to andenhancing facilitators of seeking mental health services. Toimprove help-seeking, the focus of strategies should be onenhancing mental health literacy, lowering stigma, andincreasing trust in mental health services’effectiveness.